1998
DOI: 10.1001/archinte.158.5.537
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Stroke in Patients Undergoing Hemodialysis

Abstract: Hospitalized patients undergoing hemodialysis in whom stroke occurs appear to have as good an outcome as that of patients with normal renal function, although they are hospitalized longer. In addition, certain clinical variables seem to be associated with a worse outcome. Aggressive measures to prevent and treat stroke seem as warranted for patients undergoing hemodialysis as for patients with normal renal function, although interventions to reduce the length of hospital stay are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Based on this study, for every 100 dialysis patients who have a stroke, thirty-five of them will die within thirty days, and only fifty-six of the one hundred patients will be able to go home or to an acute rehabilitation facility. While this low “successful recovery” rate is similar to that found in an earlier single-center cohort of prevalent hemodialysis patients followed in New York,27 it is inferior to the 10% adjusted stroke case-fatality rate seen in the Atherosclerosis Risk in Communities (ARIC) cohort28 and the 20% of patients requiring institutional care in the general population 28. This likely reflects the comorbid conditions that our patients on dialysis accumulated before they experienced a stroke.…”
Section: Discussionsupporting
confidence: 67%
“…Based on this study, for every 100 dialysis patients who have a stroke, thirty-five of them will die within thirty days, and only fifty-six of the one hundred patients will be able to go home or to an acute rehabilitation facility. While this low “successful recovery” rate is similar to that found in an earlier single-center cohort of prevalent hemodialysis patients followed in New York,27 it is inferior to the 10% adjusted stroke case-fatality rate seen in the Atherosclerosis Risk in Communities (ARIC) cohort28 and the 20% of patients requiring institutional care in the general population 28. This likely reflects the comorbid conditions that our patients on dialysis accumulated before they experienced a stroke.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, nontradition risk factors, including the uraemic process 8,9 and the dialysis process itself, 10 may predispose patients undergoing dialysis to stroke. Several studies have found that the incidence of stroke in patients with ESRD is much greater than that in the general population 11–18 . However, only few studies have characterized stroke subtypes and existing studies lack consistency.…”
mentioning
confidence: 99%
“…29,30 In addition, although hemodialysis ameliorates many of the metabolic disturbances of uremia, patients with ESRD have a substantially higher risk for death due to cerebrovascular disease than does the general population. 31,32 In addition to the APACHE II score and history of stroke, we found that postoperative RUO, even at low levels, was an independent predictor of lower 30-day mortality rate in maintenance hemodialysis patients. The OR of 30-day mortality was 4.56 for patients with postoperative anuria.…”
Section: Discussionmentioning
confidence: 73%